Faktor Personal, Perilaku, Lingkungan dan Perilaku Diet Mahasiswa - Saputri, Retvika Vallentina; Purwito, Dedy (Jurnal Ilmiah Wahana Pendidikan, 2024)
Background: During adolescence, there are changes in lifestyle and diet that can affect nutritional status problems such as obesity and psychosocial problems such as dissatisfaction with body shape. Teenagers who experience this tend to go on a diet. There are several factors related to dietary behavior by adolescents, such as personal factors (level of nutritional knowledge), behavioral factors (self-efficacy, food preparation), and environmental factors (friends of the same age). Objective: To determine the correlation between personal (knowledge of nutrition), behavior (self-efficacy, food preparation), and environmental (peers) factors with the dietary behavior of undergraduate nursing students. Methods: This was quantitative research with a correlation description with a cross- sectional study approach. Sampling used proportional allocation method with 251 students in semesters 1, 2, and 3 of the undergraduate Nursing study program. The research instrument used a Google Form questionnaire.Results: The results of the study showed that the majority of respondents were female and 19 years old. Most of the respondents carried out dieting behavior for reasons because they were dissatisfied with their body shape. The results of the Chi-Square test obtained a p- value of 0.001 (0.05) which indicated a correlation between nutritional knowledge, self- efficacy, food preparation, peers, and dietary behavior.Conclusion: Personal factors (level of knowledge of nutrition), Behavior factors (self- efficacy, food preparation), and Environmental factors (peers) are factors that influence adolescents in carrying out their dietary behavior.